Exploring the color of plant powders using computer colorimetry - Niemirich, Oleksandra; Petrusha, Oksana; Vasheka, Oksana; Trofimchuk, Lyudmila; Myndrul, Natalia (My University, 2016)
The results of the determination of the colour of vegetable powders from vegetables and fruits using modern digital technology. The values of the colour coordinates of powders in dry and reconstituted species, as well as in prepared dishes, are determined. The prospects for using the methodology for determining the color of raw materials, semi-finished products and finished products for quality control of production are justified.
Keywords: колірні координати; комп'ютерна колориметрія; індекс жовтизни; рослинні порошки; цифрове зображення; колір; цветовые координаты; компьютерная цветометрия; индекс желтизны; растительные порошки; цифровое изображения; цвет; color coordinates; computer colorimetry; yellowness index; vegetable powders; digital image; colour; кафедра експертизи харчових продуктів; кафедра технології ресторанної і аюрведичної продукції